Lack of acute xenogeneic graft‐versus‐host disease, but retention of T‐cell function following engraftment of human peripheral blood mononuclear cells in NSG mice deficient in MHC class I and II expression. Issue 3 (1st November 2018) - Brehm, Michael A.; Kenney, Laurie L.; Wiles, Michael V.; Low, Benjamin E.; Tisch, Roland M.; Burzenski, Lisa; Mueller, Christian; Greiner, Dale L.; Shultz, Leonard D.
ABSTRACT: Immunodeficient mice engrafted with human peripheral blood mononuclear cells (PBMCs) support preclinical studies of human pathogens, allograft rejection, and human T‐cell function. However, a major limitation of PBMC engraftment is development of acute xenogeneic graft‐ versus ‐host disease (GVHD) due to human T‐cell recognition of murine major histocompatibility complex (MHC). To address this, we created 2 NOD‐ scid IL‐2 receptor subunit γ ( IL2rg ) null (NSG) strains that lack murine MHC class I and II [NSG–β‐2‐microglobulin ( B2M ) null ( IA IE ) null and NSG‐( K b D b ) null ( IA null )]. We observed rapid human IgG clearance in NSG‐ B2M null ( IA IE ) null mice whereas clearance in NSG‐( K b D b ) null ( IA null ) mice and NSG mice was comparable. Injection of human PBMCs into both strains enabled long‐term engraftment of human CD4 + and CD8 + T cells without acute GVHD. Engrafted human T‐cell function was documented by rejection of human islet allografts. Administration of human IL‐2 to NSG‐( K b D b ) null ( IA null ) mice via adeno‐associated virus vector increased human CD45 + cell engraftment, including an increase in human regulatory T cells. However, high IL‐2 levels also induced the development of GVHD. These data document that NSG mice deficient in murine MHC support studies of human immunity in the absence of acute GVHD and enable evaluation of human antibody therapeutics targeting human T cells.—Brehm, M. A., Kenney, L. L., Wiles, M. V., Low, B. E., Tisch, R. M., Burzenski, L., Mueller, C., Greiner, D. L., Shultz, L. D. Lack of acute xenogeneic graft‐ versus ‐host disease, but retention of T‐cell function following engraftment of human peripheral blood mononuclear cells in NSG mice deficient in MHC class I and II expression. FASEB J. 33, 3137–3151 (2019). www.fasebj.org